Beyond the Presidential Threshold: How Cebong and Kampret Political Identities Shape Social Media Discourse - Urai Panzi; Jagad Aditya Dewantara; sulistyarini sulistyarini; Wibowo Heru Prasetiyo; Jacob Shimrumun Loraa (Politicon : Jurnal Ilmu Politik, 2023)
The polemic regarding the Presidential Threshold policy has caused conflict in society and hampered Indonesia's political development. This study aims to prove the impact of the Presidential Threshold policy on the political identity of two groups of people who are often referred to as "cebong" and "kampret". The impact of this policy has led to polarization of netizens and heated and uncontrolled communication patterns on social media. This study uses the netnographic method with a critical discourse approach to determine the impact of the policy. The results showed that the Presidential Threshold policy had an impact on the inconsistency of political parties, there were only 2 pairs of candidates in the presidential election, injured small parties because of oligarchic efforts, many negative comments were hostile on social media and researchers found Presidential Threshold policies gave birth to a Political Identity "cebong- kampret, which can cause the Indonesian nation to experience segregation which creates conflict in society and of course triggers national disgrace on social media. With the existence of a Presidential Threshold policy, the government must consider the presentation of 20%, this can reduce the polarization that exists in society.